Mortality from oral and oropharyngeal cancer: age-period-cohort effect, Brazil, 1983–2017 - Perea, Lillia Magali Estrada; Antunes, José Leopoldo Ferreira; Peres, Marco Aurelio (Revista de Saúde Pública, 2021)
OBJECTIVE Estimate the effect of age, period, and birth cohort on mortality from oral and oropharyngeal cancer in Brazil and its macro-regions. METHODS Deaths from oral and oropharyngeal cancer from 1983 to 2017 were analyzed. The Poisson regression model was applied, using estimable functions proposed by Holford. RESULTS From 1983 to 2017, 142,634 deaths from oral and oropharyngeal cancer were registered in Brazil, 81% among men, and the South and Southeast regions had the highest rates. The most significant period effects were observed in male mortality in the Southeast and Central-West regions for the 2003–2007 reference period. In the North, Northeast, and Central-West regions, an increased risk of mortality was observed in the most recent male cohorts. In the North region, the most significant risk identified was for men born during 1973–1977 (RR = 1.47; 95%CI 1.05–2.08); in the Northeast, for men born during 1988–1992 (RR = 2.77; 95%CI 1.66–4.63); and in the Central-West, for women born during 1973–1977 (RR = 2.01; 95%CI 1.19–3.39). In the Southeast and South regions, the most recent cohorts had lower mortality rates. The lowest risk in the Southeast region was observed in the male cohort born during 1978–1982 (RR = 0.53; 95%CI 0.45–0.62) and 1983–1987 in the South region (RR = 0.25; 95%CI 0.12–0.54). CONCLUSIONS Age had a significant effect on mortality from oral and oropharyngeal cancer in all regions. In the North, Northeast, and Central-West regions, an increase in risk was observed in the most recent cohorts, while in the South and Southeast regions, these cohorts presented a lower risk when compared to the older cohorts.